New Life Through Disaster: A Thematic Analysis of Women's Experiences of Pregnancy and the 2016 Fort McMurray Wildfire - Pike, Ashley; Mikolas, Cynthia; Tompkins, Kathleen; Olson, Joanne; Olson, David M.; Brémault-Phillips, Suzette (Frontiers in Public Health, 2022)
Background: During May 2016, residents of Fort McMurray Wood Buffalo, Alberta were evacuated due to an uncontrolled wildfire. The short-notice evacuation had destabilizing consequences for residents, including changes in routines, loss of control, and increased uncertainty. These destabilizing consequences were especially detrimental to women who were pregnant or preconception during the evacuation. Pregnant and preconception women are particularly susceptible to a vast range of negative consequences during and post natural disasters, including elevated stress and higher incidence of pregnancy complications including gestational diabetes mellitus, pregnancy induced hypertension and C-section. The aim of this study was to understand the experiences, perceived stress and resilience of women who were pregnant during the 2016 wildfire, and promote the health of pregnant women inform future interventions to enhance resilience and promote health of pregnant women in the face of natural disasters. Methods: A qualitative thematic analysis of 16 narratives penned by pregnant women and recounted in Ashley Tobin’s compilations 93/88,000 and 159 More/ 88,000: Stories of Evacuation, Re-Entry and the In-Between was conducted. Results: Analysis of findings revealed five key themes: 1) stress responses due to personal and external factors, 2) social connectedness and support as a facilitator of resilience, 3) performance of resilience-enhancing activities, 4) the roles of pregnancy and motherhood in the experiences of loss and resilience, and 5) the importance of home. Conclusion: Pregnant women have unique barriers that may negatively impact them during a natural disaster or other form of stressful event. They may benefit from assistance with navigating role transition during pregnancy, training in stress management strategies, and writing interventions to build resiliency and begin the process of recovery from trauma.